2000
DOI: 10.1111/j.1365-2338.2000.tb00907.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis and control of bacterial speck, Pseudomonas syringae pv. tomato, on tomato*

Abstract: Bacterial speck of tomato, caused by Pseudomonas syringae pv. tomato, was observed to cause severe symptoms, especially on protected tomato crops, during the winter season in the coastal area of Lebanon. This study was conducted to investigate the aetiology and pathogenesis of the bacterium involved and the efficacy of different chemicals for the control of the disease. Biochemical, physiological and pathological tests verified the identity of the bacterium involved as P. s. tomato. Periodic histological secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…tomato. These results are agree with those reported by Saad and Hassan, 2000;and Schaad, 1988. Pathogenicity tests revealed that the Pst DC3000 was the most virulent isolate compared to Egyptian isolates. Tomato speck disease is worldwide that favored by low to moderate tem-peratures and high moisture conditions (Babelegoto et al, 1988;and Jones et al,1991).…”
Section: Discussionsupporting
confidence: 94%
“…tomato. These results are agree with those reported by Saad and Hassan, 2000;and Schaad, 1988. Pathogenicity tests revealed that the Pst DC3000 was the most virulent isolate compared to Egyptian isolates. Tomato speck disease is worldwide that favored by low to moderate tem-peratures and high moisture conditions (Babelegoto et al, 1988;and Jones et al,1991).…”
Section: Discussionsupporting
confidence: 94%
“…Control of bacterial speck is usually accomplished by copper-based pesticides as well as mancozeb, zineb, and some antibiotics (Jardine and Stephens 1987;Saad and Hassan 2000). However, when environmental conditions favor disease development and inoculum levels are high, standard treatments are not always effective (Jardine and Stephens 1987).…”
Section: Introductionmentioning
confidence: 99%